THE EFFECT OF PROBING PROMPTING ON STUDENTS’ WRITING ACHIEVEMENT AT TENTH GRADE OF MAN 1 BOMBANA - Hasnia, Hasnia; Mursalim, Mursalim; Agustina, Sitti (Journal of Teaching of English, 2020)
The objective of this research was to find out the effect of using probing prompting on students’ writing achievement at tenth grade of MAN 1 Bombana. This research applied quasi experimental design that consist of experimental class and control class. The sample of this research were students at class X IPA and X IPS in MAN 1 Bombana who were register in academic years 2019/2020. The sample taken by using cluster random sampling and the total numbers of students are 46, 22 for experimental class (X IPA) and 24 for control class (X IPS). The research instrument was written test which focus on narrative text. The researcher collected the data by giving pre-test in both of the classes, giving treatment in experimental by giving probing prompting and non-probing prompting in control class, and giving post-test in both of the classes. In analyzing the data were used SPSS 16.0 version. To examine the hypothesis the researcher used an independent sample t-test. Based on the result, it showed that students’ mean score of post-test in experimental class is 64.35. It is raised 9.83 point from its pre-test (54.52). While students’ mean score of post-test in control class is 56.82. It is only raised 4.97 point from its pre-test (51.85). Besides, the value of degree of freedom (df)= 42, t=4.574, and sig (2 tailed)=0.000. It means that the probability (sig) value is lower than α ( p value < α or 0.000 < 0.05). Therefore,probingprompting  had a significant effect on students’ writing achievement at tenth grade of MAN 1 Bombana.